HUBUNGAN PERSEPSI KONSUMEN TERHADAP PRODUK OLEH OLEH KHAS BOGOR DENGAN PENGAMBILAN KEPUTUSAN PEMBELIAN - Novitasari Novitasari; Diana Amaliasari; Dwi Rini Sovia Firdaus (UNIVERSITAS PAKUAN, 2020)
This study aims to determine the characteristics of consumers and consumer perceptions in making decisions about purchasing traditional food of Bogor, figure out the purchase decisions of traditional food of Bogor, find the correlation between characteristics and perceptions of consumers in decision-making of Bogor traditional food. Tourists who visited Bogor became the populations of this research. The samples are100 people using the Probability Sampling technique: Stratified random sampling. The results showed that the characteristics of consumers were dominated by women with an average age of 23-28 years, with Diploma / Bachelor education, with an average monthly income of Rp. 3,000,000-Rp. 4,000,000 and working as a private employee. Consumer perception in purchasing decisions of traditional food of Bogor showed the